1998
DOI: 10.1002/jlb.64.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Resident mast cells are important for eotaxin-induced eosinophil accumulation in vivo

Abstract: Eotaxin administration intraperitoneally, but not into dorsal air-pouches, of ovalbuminsensitized mice exhibiting blood eosinophilia induced a threefold increase in eosinophil (E s) infiltration. Transfer of 1 ؋ 10 6 mixed peritoneal cavity cells (PCC), containing 3.5 to 4.5 ؋ 10 4 mast cells (MC), from donor mice to air-pouches of sensitized (but not unsensitized) recipient mice, established an E infiltration to eotaxin (vehicle, 0.86 ؎ 0.27 ؋ 10 6 ; eotaxin, 1.63 ؎ 0.16 ؋ 10 6 E s/air-pouch). Neutrophil numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
5
21
0
2
Order By: Relevance
“…injection of MIP-1␣, RANTES, or eotaxin induced a significant dose-dependent accumulation of eosinophils 48 h after challenge. The effects of MIP-1␣ and eotaxin are in agreement with previous studies demonstrating the ability of these chemokines to induce eosinophil recruitment directly, by activating specific receptors on eosinophils, or indirectly, by activating intermediate cell types, such as mast cells (5,(21)(22)(23). In contrast, RANTES does not appear to stimulate murine (24) or guinea pig (25) eosinophils directly, suggesting that the ability of this chemokine to induce eosinophil migration most likely depends on its action on an intermediate cell type.…”
Section: Discussionsupporting
confidence: 90%
“…injection of MIP-1␣, RANTES, or eotaxin induced a significant dose-dependent accumulation of eosinophils 48 h after challenge. The effects of MIP-1␣ and eotaxin are in agreement with previous studies demonstrating the ability of these chemokines to induce eosinophil recruitment directly, by activating specific receptors on eosinophils, or indirectly, by activating intermediate cell types, such as mast cells (5,(21)(22)(23). In contrast, RANTES does not appear to stimulate murine (24) or guinea pig (25) eosinophils directly, suggesting that the ability of this chemokine to induce eosinophil migration most likely depends on its action on an intermediate cell type.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies suggest that eosinophil migration is in part regulated by the ability of resident mast cells to secrete chemoattractants for eosinophils, such as eotaxin and leukotrienes. [37][38][39][40] We also noted that, on days 7 and 8 of the infection with 10 000 S.v. L3, parasite egg production in IL-3 þ / þ mice was B3-fold that in the IL-3À/À mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although this has been observed in the lung following aerosolized OVA challenge (Kung et al, 1994), our finding is the first to suggest a role for mast cells in eotaxin-elicited pulmonary eosinophilia. Mast cells also appear to fill a similar role in the peritoneum following eotaxin challenge (Harris et al, 1997;Das et al, 1998). Tryptase/chymase-double positive human mast cells express CCR3 (Ochi et al, 1999;Romagnani et al, 1999), which is functionally active in chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…administration of other known CCR3 ligands, murine RANTES, or macrophage inflammatory protein-1␣ to OVAsensitized mice did not result in an appreciable E⌽ influx: 10 g of eotaxin (n ϭ 8) and 10 g of RANTES (n ϭ 5) elicited 18.0 Ϯ 4.0 ϫ 10 4 and 1.0 Ϯ 0.7 ϫ 10 4 E⌽ in the BAL, respectively, and 10 g of eotaxin (n ϭ 6) and 10 g of macrophage inflammatory protein-1␣ (n ϭ 6) elicited 14.2 Ϯ 6.6 ϫ 10 4 and 0.8 Ϯ 0.6 ϫ 10 4 E⌽ in the BAL, respectively. Previous studies have shown a role for endogenous mast cells in mediating eotaxin-mediated E⌽ migration into the peritoneal cavity (Das et al, 1997b(Das et al, , 1998Harris et al, 1997). To investigate the role of mast cells in mediating eotaxininduced lung eosinophilia, mast cell-deficient W/W v mice were used.…”
Section: Development and Characterization Of A Model Of Ccr3-dependenmentioning
confidence: 99%